PERAN MGMP SEBAGAI KOMUNITAS BELAJAR PROFESIONAL DALAM PENGEMBANGAN KAPASITAS GURU EKONOMI DI KABUPATEN SANGGAU - Munawar Thoharudin; Achmadi Achmadi; Dewi Puji Astuti; Al Farizi (STKIP Persada Khatulistiwa Sintang, 2025)
The This research aims to analyze the role of the Subject Teachers' Conference (MGMP) in supporting the professional and career development of teachers, especially in Sanggau Regency, West Kalimantan. Using an interpretive qualitative approach with a case study design, data was collected through in-depth interviews, participant observation and documentation studies, then analyzed using thematic analysis techniques. The research results show that MGMP functions as a collaborative space that strengthens pedagogical reflection, professional solidarity, and growth in teacher competence, but its effectiveness is still limited by geographic, institutional constraints, and the lack of expert facilitators. These findings indicate that the implementation of the MGMP has reflected some of the principles of the Professional Learning Community (PLC) and Continuous Professional Development (CPD), although it has not been structured systematically. This research advocates a MGMP strengthening model based on three main dimensions—reflective collaboration, participative leadership, and systemic support—as a conceptual framework for professional teacher development in rural areas. With the support of multi-level policies and digital innovation, MGMP has the potential to transform into an adaptive, inclusive and sustainable professional learning ecosystem to improve the equality and quality of national education